Cascading effects from plant to soil elucidate how the invasive Amorpha fruticosa L. impacts dry grasslands. (1st May 2020) - Boscutti, Francesco; Pellegrini, Elisa; Casolo, Valentino; de Nobili, Maria; Buccheri, Massimo; Alberti, Giorgio
Abstract: Questions: Understanding the mechanisms underlying the impacts of exotic plant invasions is a central issue in plant ecology. Considering the invasion process, any alteration of the nutrient cycle is of fundamental importance. We hypothesized that the woody N‐fixing invasive Amorpha fruticosa is indirectly depleting plant diversity by altering ecosystem functions of riverine grasslands, thus producing a conspicuous shift in species composition. Location: Temperate lowland riparian areas of northeast Italy. Methods: In 12 sites, we selected uninvaded, partially invaded, and invaded grasslands (36 plots). In each plot, we performed a vegetation relevé, measured main A. fruticosa growth traits, light transmittance and soil features. We studied the effects of the invasion of A. fruticosa on grassland properties and plant diversity, examining the interactions between soil nutrient cycles, light availability and plant diversity. Results: Increased abundance of A. fruticosa affected main soil properties (i.e. increase in soil mineralization and nitrification) and light availability (i.e. decrease in light). The δ 15 N of soil organic matter was strongly related to A. fruticosa basal area, thus supporting the hypothesis of an increase in soil nitrogen (N) availability due to invasion by the N‐fixer. Plant taxonomical and functional diversity decreased significantly as A. fruticosa cover increased. Plant diversity was more related with N than light availability or soil organic carbon. Similarly, the shift in species composition (i.e. beta diversity) of invaded grasslands was related to increased soil nitrification rates. Conclusions: Our findings show how a nitrogen‐fixing invasive plant such as A. fruticosa may influence the main ecosystem properties, causing cascading effects on soil functions, decreasing plant diversity. Alteration of the N cycle represents the key process involved in this plant invasion, suggesting that further studies should focus on potential solutions to mitigate the soil N supply, curb the invasion and restore plant diversity of these riverine grasslands. Abstract : We studied the effects of the invasion of Amorpha fruticosa on riverine ecosystem proprieties and plant diversity, considering the interactions between soil nutrient cycles, light availability and plant diversity. Our findings show that a nitrogen‐fixing invasive plant such as A. fruticosa may influence the main ecosystem proprieties, causing cascading effects on soil functions and the collapse of ecosystem plant diversity.